Application of ANFIS for Distance Relay Protection in Transmission Line - Azriyenni Azriyenni; Mohd Wazir Mustafa (Institute of Advanced Engineering and Science, 2015)
The techniques hybrid intelligent was introduced in transmission protection that usage in electric power systems. There was applied ANFIS for distance relay protection particularly for transmission line. If a fault occurs during the transmission line identification caused by unwanted fault thus the power delivery to the consumer becomes not going well. Therefore, it would need to provide an alternative solution to fix this problem. The objective of this paper uses impedance transmission line to determine how long the channel spacing will be protected by distance relay. It has been distance relays when fault occurs in transmission line with the application Sugeno ANFIS. The simulation shows it excellent testing results can be contributed to an alternate algorithm that it has good performance to protecting system in transmission line. This application used by using software Matlab.